1998
DOI: 10.1023/a:1000881918216
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: It has been found previously that a significant number of Micrococcus luteus cells starved in a prolonged stationary phase (up to 2 months) and then held on the bench at room temperature without agitation for periods of up to a further 2-7 months can be resuscitated in liquid media which contained (statistically) no initially-viable (colony-forming) cells but which were fortified with sterile supernatant from the late logarithmic phase of batch growth. Here it was found that such resuscitation can be done only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 74 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…Cells in the dormant state have a much thicker cell wall compared to active cells. 16,25,26 The overall cell conductivity increases with an increase in the thickness of cell wall, 20,27,28 and thus the increase in the bacterial conductivity from active to dormant state can have been caused by an increase in wall thickness. The results obtained tie in with previous studies, in which the particle conductivity of M. luteus ͑but not E. coli͒ greatly increased when the cells went from exponential to stationary phase.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cells in the dormant state have a much thicker cell wall compared to active cells. 16,25,26 The overall cell conductivity increases with an increase in the thickness of cell wall, 20,27,28 and thus the increase in the bacterial conductivity from active to dormant state can have been caused by an increase in wall thickness. The results obtained tie in with previous studies, in which the particle conductivity of M. luteus ͑but not E. coli͒ greatly increased when the cells went from exponential to stationary phase.…”
Section: Discussionmentioning
confidence: 99%
“…To obtain active cells M. smegmatis cells were cultured [12][13][14][15][16] in 100 ml glass flasks with loose caps for 24 h at 37°C on an orbital incubator shaker at 200 rpm in 20 ml of the rich medium nutrient broth E LabM, supplemented with 0.05 % ͑v/v͒ Tween-80. To obtain dead M. smegmatis cells, a 24-h-old active culture was autoclaved at 126°C for 30 min.…”
Section: A Cell Culturementioning
confidence: 99%
See 1 more Smart Citation
“…Kell and co-workers showed unequivocally that starved non-culturable cells of the Gram-positive organism Micrococcus luteus could be recovered in growth medium, provided that some filtered medium from a culture growing in late exponential phase was added (Kaprelyants et al, 1994) or that some viable cells were present (Votyakova et al, 1994). It was concluded that medium from exponentially growing cultures may promote resuscitation by overcoming the effect of an antibacterial factor that otherwise caused self-poisoning of dormant cells during resuscitation (Mukamolova et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…6 The "resuscitation promoting factor" ͑RPF͒ that is involved has been successfully isolated from supernatant of M. luteus and characterized by Mukamolova et al 7 RPFs have been found to be a family of proteins whose homologous genes are widespread among the guanine-cytosine ͑GC͒-rich Gram-positive bacteria, including streptomycetes, corynebacteria, and mycobacteria. 8 They stimulate cell growth and cell multiplication at very low concentrations and are active toward different strains of bacteria. 7 The analysis of the structure of the RPFs has revealed that they may be peptidoglycan hydrolases and may actively participate in the modification of the thickened cell wall of the NC cells during resuscitation.…”
Section: Introductionmentioning
confidence: 99%